The importance of health status for the financial sustainability of the pension system: A case study of Romania in the context of the EU - Iuliana-Claudia Mihalache; Felicia-Cătălina Apetroi; Mihaela Tomaziu-Todosia; Olesea Plotnic (CES Working Papers, 2020)
Based on the need for a prosperous economy, it is important to increase the quality of life of the active population in particular, but also of the inactive, in order to reduce the consumption of free and/or reimbursed medicines. In this regard, social security and protection systems need to consider improving working conditions, expanding the network of medical services, creating medical, social and professional recovery systems, continuously improving the material and medical situation of people, in order to increase the time of productive activity. This study aims to analyse the evolution of pension categories in Romania for the period 1990-2018, as well as the correlation between health and financial sustainability of the pension system, with an emphasis on healthy life expectancy. In order to develop the case study, the authors consider the evolution of this system in the last decade in Romania, following the average number of people retiring early, as well as people receiving disability pensions.
Keywords: 330; economy; health; financial sustainability; pensions